(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The article analyzes the essence of the formation of commemorative culture of the Kyrgyz, which is still a little-studied phenomenon in science. The research task was an attempt to determine the trajectory of commemorative practice, which has acquired particular significance in the era of globalization. As today it is difficult to find a common understanding of the essence of historical memory as a form of new thinking, a new worldview in the culture of the Kyrgyz people. This scientific article interprets its own emphasis in understanding the formation of a commemorative culture based on the educational and pedagogic potential of the nation. The main attention is paid to the characteristics of commemoration from the position of other researchers, in particular, defining this phenomenon as relevant in the education and formation of value systems of a modern person. In conclusion, the need to form a common vision of commemorative culture in the realities of the 21st century is traced.